2007
DOI: 10.1021/ja069048o
|View full text |Cite
|
Sign up to set email alerts
|

A Nearly Isosteric Photosensitive Amide-Backbone Substitution Allows Enzyme Activity Switching in Ribonuclease S

Abstract: psi[CS-NH]4-RNase S, a site specific modified version of RNase S obtained by thioxylation (O/S exchange) at the Ala4-Ala5- peptide bond, was used to evaluate the impact of protein backbone photoswitching on bioactivity. psi[CS-NH](4)-RNase S was yielded by recombination of the S-protein and the respective chemically synthesized thioxylated S-peptide derivative. Comparison with RNase S revealed similar thermodynamic stability of the complex and an unperturbed enzymatic activity toward cytidine 2',3'-cyclic mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 58 publications
(141 reference statements)
2
75
0
Order By: Relevance
“…Deuteration of amide protons destabilizes helical structures, but the effect is very small (14). A near isosteric change in the polypeptide backbone can be achieved by introducing a thioxopeptide bond, i.e., by replacing an amide oxygen by sulfur (15).…”
mentioning
confidence: 99%
“…Deuteration of amide protons destabilizes helical structures, but the effect is very small (14). A near isosteric change in the polypeptide backbone can be achieved by introducing a thioxopeptide bond, i.e., by replacing an amide oxygen by sulfur (15).…”
mentioning
confidence: 99%
“…[48,49] It has recently been shown that this isomerization near the N-terminus of the S peptide in the protein complex ribonuclease S induces conformational changes sufficient to switch off enzymatic activity. [50] In many of these examples photo-excitation of a significant fraction of molecules is possible, resulting in large conformational changes and transient VCD signal levels can be similar to those observed in the Co(sp)Cl 2 model compound. In addition, the development of alternative detection schemes is about to further improve signal to noise levels in transient circular dichroism measurements.…”
Section: Photo-triggered Conformational Transitions Of Peptidesmentioning
confidence: 88%
“…The N-terminal peptide comprising residues 1-20 (MjCM [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ) was prepared by solid-phase peptide synthesis (SPPS) methods, and purified by HPLC. The C-terminal portion containing the additional mutation I77R to disfavor homodimerization 18 (MjCM * 22-93 ) was produced by heterologous expression in the CM-deficient Escherichia Coli strain KA13 27 with a C-terminal His 6 -tag and purified on a Ni-NTA column.…”
Section: Design Of a Heterodimeric Chorismate Mutasementioning
confidence: 99%
“…Solid-phase peptide synthesis mMjCM [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] was synthesized on a Wang resin preloaded with Fmoc-Leu (0.68 mmol/g) on a 433A peptide synthesizer (Applied Biosystems) on a 0.1 mmol scale with standard Fmoc-protected amino acids (Novabiochem). The peptide was cleaved from the resin and amino acid protecting groups were removed by incubation in 95% TFA, 2.5% H 2 O, and 2.5% TIS for 2 h. The resin was filtered off, excess TFA was evaporated, and the peptide was precipitated and washed with cold ether and dried under vacuum.…”
Section: In Vivo Complementation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation